79角二()元()角
65角二()元()角
64分二()角()分
23分二()角()分
52分二()角()分
73分二()角()分
元二()角
2. 00 元=()元
元=()分
()角()79角二()元()角
65角二()元()角
64分二()角()分
23分二()角()分
52分二()角()分
73分二()角()分
元二()角
2. 00 元=()元
元=()分
()角()分
=()元()角
元=()元()角
元=()元()角()
5分+5分=()角
5分+3分=()分
5分+8分=()分
9分—4分=()分
8角一3角二()角
1元-3角=()角
6角+ 2角=()角
13角一9角=()角
一 5角+2角=()角
18角一7角=()角
10角一9角=()角
6角+ 7角=()角
9角+ 8角=()角
5角+5角=()元
1角一7分=()分
1角一3分=()分
1元一6角=()角
2元+ 10元=()元
7元—5元=()元
17元—7元=()元
13元+7元=()元
6元—2元=()元
分 29元—20元=()元
10元—2元=()元
2元+ 10元=()元
20元—10元二元
1元-9角=()角
1角一9分=()分
1元—8角=()角
9分+5分=()角()分
6分+5分=()角()分
9分+5分=()角()分
6分+7分=()角()分
8角+ 4角=()元()角
7角+9角=()元()角
2角+9角=()元()角
4角+ 7角=()元()角
4角+ 9角=()元()角
4元+8角=()元()角
1角5分-4分=()角()分
1元4角+ 6角=()角=()元
2元2角一2角二()元
1元3角+7角=()角=()元
8角5分-4分=()角()分
1角2分-6分=()分
7元2角+3元=()元()角
1角5分—5分二()角
1角3分—5分=()分
1角8分-6分=()分
1元5角+2元5角=()元
3元4角-5角=()元()角
8分+9分=()角()分
6元9角+5角=()元()角
二年级元角分计算题 来自淘豆网m.daumloan.com转载请标明出处.